Cerminan Pernikahan Orang Tua: Bagaimana Status Perkawinan Orang Tua Membentuk Sikap Anak Dewasa Awal Terhadap Pernikahan - Insani Natalia Pakombong; Arie Gunawan Hazairin Zubair; Tarmizi Thalib (SEED: Journal of Scientific Research, 2026)
This study aims to determine the differences in attitudes towards marriage among young adults based on their parents’ marital status. The background of this study is the increasing divorce rate in Indonesia, which affects young people’s perspectives on marriage. The research method used was quantitative comparative with purposive sampling, involving 468 unmarried young adults in Makassar City. The instrument used was the General Attitudes Towards Marriage Scale (GAMS), which had been tested for validity and reliability (Cronbach’s Alpha = 0.897). The results of the hypothesis test showed a significance value of 0.020 (p < 0.05), indicating a significant difference between respondents with intact parents and those with divorced parents. Respondents with intact parents showed a more positive attitude towards marriage compared to those with divorced parents. These findings highlight that parental marital status plays an important role in shaping young adults’ perspectives on marriage.